2015
DOI: 10.1177/2055116915597239
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous thoracolumbar hematomyelia secondary to hemophilia B in a cat

Abstract: Case summaryA 10-year-old neutered male domestic shorthair cat presented for evaluation of acute onset of paraplegia with loss of nociception and thoracolumbar spine hyperesthesia and no history of trauma. Activated partial thromboplastin time (aPTT) was markedly prolonged, and specific coagulation factor testing revealed a factor IX level of 4% of normal activity, confirming the presence of mild hemophilia B. Prior abnormal bleeding had occurred at the time of castration as a kitten, as well as with laceratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…In the absence of trauma, conditions described to be associated with intramedullary spinal cord haemorrhage include neoplasia, vasculitis, 9 parasite infection 10 and haemophilia. 11 In the present case, intramedullary haemorrhage developed <24 h after trauma and this correlates well with the description of rapidly developing parenchymal haemorrhages after experimental SCI. Indeed, in rats, two studies focused on MRI findings after SCI, 12 and these found a good correlation between MRI and histopathological findings.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the absence of trauma, conditions described to be associated with intramedullary spinal cord haemorrhage include neoplasia, vasculitis, 9 parasite infection 10 and haemophilia. 11 In the present case, intramedullary haemorrhage developed <24 h after trauma and this correlates well with the description of rapidly developing parenchymal haemorrhages after experimental SCI. Indeed, in rats, two studies focused on MRI findings after SCI, 12 and these found a good correlation between MRI and histopathological findings.…”
Section: Discussionsupporting
confidence: 90%
“…In the absence of trauma, conditions described to be associated with intramedullary spinal cord haemorrhage include neoplasia, vasculitis, 9 parasite infection 10 and haemophilia. 11 …”
Section: Discussionmentioning
confidence: 99%
“…As in the case described here, hyperesthesia together with neurological deficits has also been reported in all the previous cases of haematomyelia described in veterinary medicine with hemophilia A and B, in two of the four cases with Angiostrongylus Vasorum, in a case of juvenile polyarteritis syndrome, and other cases of unknown origin [ 5 , 7 – 9 ]. Haematomyelia has been described in human medicine as an abrupt spinal syndrome, with intense local or radicular pain related to motor and sensory deficits, which in time and depending on its location [ 10 ] could be accompanied by urinary and/or faecal sphincter atony.…”
Section: Discussionsupporting
confidence: 84%
“…Haematomyelia, and in particular nontraumatic haematomyelia, is rarely reported in veterinary medicine [ 1 3 ]. Previously reported underlying causes for nontraumatic haematomyelia include vascular malformations [ 3 ], spinal tumors [ 4 ], parasites such as Angiostrongylus vasorum [ 5 ] and Leishmania infantum [ 6 ], and also related to juvenile polyarteritis syndrome [ 7 ] and congenital coagulopathies such as Von Willebrand disease or hemophilia A and B [ 8 , 9 ]. Recently, a case of suspected primary haematomyelia has also been described in a French Bulldog with no identified underlying cause [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation